The Activities of Military Management Bodies to Mobilize Military Builders to Create an Insurmountable Defense on the Kursk Arc - V. P. Gridnev (Управленческое консультирование)
The relevance of the topic is explained by the fact that in modern conditions the citizens of Russia need to turn to traditional values, such as Russian patriotism, service to the Fatherland and respon- sibility for its fate, historical memory, continuity of generations, unity of the peoples of the Russian Federation. All these values were demonstrated by the Soviet multinational people during the Great Patriotic War. Thus, military builders during the Battle of Kursk showed courage and labor heroism, creating defensive lines for the troops of the fronts, which inflicted a severe defeat on the Nazi troops on the Kursk Bulge. In addition, the warrior-builders actively participated in subscribing to the Second State Military Loan, in raising funds for the fund for helping orphaned children, etc.